(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
The purpose of this study is to analyze the economic burden on people in Telangana due to diabetes. In Telangana, a prospective observational study was conducted by collecting patient data. 252 patient’s data was gathered in 6 months period. This data includes health care costs and complications that is both microvascular complications (Neuropathy, Retinopathy & Nephropathy) and macrovascular complications (Coronary heart disease, Congestive heart failure, Myocardial infarction & Peripheral artery disease). The collected data consists of direct and indirect costs which was analyzed & calculated average cost spent in the treatment of diabetic patients. All the type 2 diabetes mellitus patients who are on anti – diabetic drugs irrespective of their co- morbidities & gender were included. Patients who are not on regular medication were excluded from the study. In this study , cost of illness of type-2 diabetes mellitus patients with & without complications were compared. The total cost of treatment per annum in patients without complications was USD 374.77 & in patients with complications was USD 497.763.